Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

vivalakoda

  • 3 years ago

Eliminate the “z” variable in the last two equations by finding opposite coefficients and adding. What is the resulting equation? x + 3y + 2z = –16 2x – y + 2z = –15 2x – 2y – z = 1 a)4x – 3y = –14 b)4x + y = –14 c)6x + 5y = 13 d)6x – 5y = –13

  • This Question is Closed

    Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy